Hybrid microspheres and percolated monoliths synthesized via Pickering emulsion co-polymerization stabilized by in situ surface-modified silica nanoparticles - B. Fouconnier; F. Lopez-Serrano; R. I. Puente Lee; J. E. Terrazas-Rodriguez; A. Roman-Guerrero; M. C. Barrera; J. Escobar (eXPRESS Polymer Letters)
The Pickering emulsion polymerization of styrene (St), divinylbenzene (DVB) as a crosslinking agent, and sodium 4-vinyl benzene sulfonate (VBS) used for in situ surface-modification of silica nanoparticles (SNps) was investigated. At 1.0 wt% DVB, amphiphilic SNps with hydrophobic patches were formed, further self-assembling into copolymer-SNps clusters occurred. Subsequently, these clusters grow by monomer swelling to finally lead to the formation of core-shell polymer microspheres. Unlike the hydrophilic patchy SNps, at 2.0 and 3.0 wt% DVB, surface-patterned SNps with higher effective hydrophobicity do not self-assemble in the water phase but rather lead to the formation of monoliths. The polymerization mechanisms related to the formation of polymer silica-coated microspheres hybrid-materials, or percolated monoliths with bi-continuous porosity, formed by interfacially jammed emulsion gel (bijels) templates, are discussed herein.